2015
DOI: 10.1136/bjophthalmol-2014-306534
|View full text |Cite
|
Sign up to set email alerts
|

The Diabetes Visual Function Supplement Study (DiVFuSS)

Abstract: BackgroundDiabetes is known to affect visual function before onset of retinopathy (diabetic retinopathy (DR)). Protection of visual function may signal disruption of mechanisms underlying DR.MethodsThis was a 6-month randomised, controlled clinical trial of patients with type 1 and type 2 diabetes with no retinopathy or mild to moderate non-proliferative retinopathy assigned to twice daily consumption of placebo or a novel, multi-component formula containing xanthophyll pigments, antioxidants and selected bota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 24 publications
0
75
1
Order By: Relevance
“…Antioxidant properties containing calcium dobesilate and A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 25 pycnogenol reduce the progression of diabetic retinopathy [100,101]. Our recent double masked study using a multi-component nutritional formula (vitamins C, D3, and E, zinc oxide, eicosapentoenoic acid, docosahexaenoic acid, alpha-lipoic acid, coenzyme Q10, zeaxanthin, lutein, benfotiamine, N-acetyl cysteine, resveratrol, turmeric root extract, green tea leaf) has shown encouraging results, as this multi-component nutritional formula can improve visual function and reduce serum inflammatory proteins in diabetic patient [102]. However, others have not observed any significant association between serum levels of major dietary antioxidants and retinopathy [103].…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…Antioxidant properties containing calcium dobesilate and A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 25 pycnogenol reduce the progression of diabetic retinopathy [100,101]. Our recent double masked study using a multi-component nutritional formula (vitamins C, D3, and E, zinc oxide, eicosapentoenoic acid, docosahexaenoic acid, alpha-lipoic acid, coenzyme Q10, zeaxanthin, lutein, benfotiamine, N-acetyl cysteine, resveratrol, turmeric root extract, green tea leaf) has shown encouraging results, as this multi-component nutritional formula can improve visual function and reduce serum inflammatory proteins in diabetic patient [102]. However, others have not observed any significant association between serum levels of major dietary antioxidants and retinopathy [103].…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…Contrast sensitivity is well correlated with various aspects of visual ability, such as orientation and mobility, reading speed, and driving (157), and with the satisfaction of individuals with their visual function and how their visual ability affects their quality of life (53). Supplements containing L and Z at various amounts and taken for three months to three years have improved contrast sensitivity in most previous studies, including in young, healthy subjects (37, 67, 94, 113, 115), in people with early (78, 116, 156) and/or advanced (12) AMD, and in individuals with diabetes (43, 77). Four of five randomized, placebo-controlled trials of solely L and/or Z isomers in >50 subjects observed improvements in spatial contrast sensitivity (77, 78, 116, 192); results of one other trial did not (135).…”
Section: Roles In Visual Healthmentioning
confidence: 96%
“…Results of some but not all intervention studies (1, 11, 115, 133, 135, 187, 192) indicate improvements in visual acuity when L and/or Z are supplemented alone (77, 113, 139) or, more often, in conjunction with other antioxidants and/or omega-3 fatty acids (1, 12, 43, 49, 147, 155). Three of seven randomized trials in >50 individuals with early or advanced AMD (116, 156) or with diabetic retinopathy (77) indicate improvements in visual acuity.…”
Section: Roles In Visual Healthmentioning
confidence: 99%
“…The results of the study showed that the multicomponent nutritional formula ameliorates glycemic control, visual function, and peripheral neuropathy in patients with diabetes (Table 2). 85 …”
Section: Histone Acetyltransferase Inhibitorsmentioning
confidence: 99%